The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fbioe.2020.00984
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Gellan Gum-Based Hydrogel With Cell Therapy for the Treatment of Cervical Spinal Cord Injury

Abstract: Cervical spinal cord trauma represents more than half of the spinal cord injury (SCI) cases worldwide. Respiratory compromise, as well as severe limb motor deficits, are among the main consequences of cervical lesions. In the present work, a Gellan Gum (GG)-based hydrogel modified with GRGDS peptide, together with adipose tissuederived stem/stromal cells (ASCs) and olfactory ensheathing cells (OECs), was used as a therapeutic strategy after a C2 hemisection SCI in rats. Hydrogel or cells alone, and a group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Olfactory ensheathing cells (OECs) are an important and clinically relevant cell transplantation population for SCI, and they can produce a suitable environment for axonal growth in the damaged CNS [ 77 ]. Studies have indicated that both collagen and fibrin hydrogels could improve the delivery [ 78 , 79 ], survival and retention of transplanted OECs for SCI.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Olfactory ensheathing cells (OECs) are an important and clinically relevant cell transplantation population for SCI, and they can produce a suitable environment for axonal growth in the damaged CNS [ 77 ]. Studies have indicated that both collagen and fibrin hydrogels could improve the delivery [ 78 , 79 ], survival and retention of transplanted OECs for SCI.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…[9] Likewise, this approach was capable of increasing diaphragmatic activity and partially restoring sensory function in cervical level 2 (C2) hemisection SCI in rats. [17] The impact of cell transplantation on regenerative processes is mainly conveyed through their secreted bioactive molecules (secretome), including soluble proteins (cytokines, growth factors, and chemokines) and a vesicular fraction (exosomes), both of which have neuroprotective, neuroregenerative, and immunomodulatory capabilities. [13,18] Thus, ASCs-derived secretome has been shown to protect pheochromocytoma (PC12) cells from glutamate excitotoxicity and apoptosis by reducing the levels of cleaved-caspase-3.…”
Section: Introductionmentioning
confidence: 99%
“…20 Based on the experience gained with the electrospinning of GG-based solutions, the present work deals with the development of a fibrous scaffold to be implanted at the site of nervous tissue injuries. It consists of electrospun nanofibers based on GG, an attractive anionic polysaccharide in neural applications, [21][22][23][24][25][26][27] and spermidine (SP), a biologic polyamine. SP was used as multifunctional agent for the preparation of nanofibers.…”
Section: Introductionmentioning
confidence: 99%